Modeling alliance activity: an iterated prisoners' dilemma with exit option - Arend, Richard J.; Seale, Darryl A. (Strategic Management Journal, 2005)
Abstract We present and solve a new, more accurate model of behavior within alliance activity. The model is essentially an iterated prisoners' dilemma with an exit option in each stage of the alliance. The proposed solution results in each partner receiving its opportunity cost as its expected average pay‐off in the alliance. Managerial implications include: identification of where to focus efforts to improve alliance cooperation and performance; and an explanation for why more sophisticated partnership strategies than tit‐for‐tat are likely to be superior in this game. Copyright © 2005 John Wiley & Sons, Ltd.